2002
DOI: 10.5194/npg-9-101-2002
|View full text |Cite
|
Sign up to set email alerts
|

Modeling stretched solitary waves along magnetic field lines

Abstract: Abstract.A model is presented for a new type of fast solitary waves which is observed in downward current regions of the auroral zone. The three-dimensional, coherent structures are electrostatic, have a positive potential, and move along the magnetic field lines with speeds on the order of the electron drift. Their parallel potential profile is flattened and cannot fit to the Gaussian shape used in previous work. We develop a detailed BGK model which includes a flattened potential and an assumed cylindrical s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
31
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 13 publications
5
31
0
Order By: Relevance
“…3(a)-4(b). The large spread in the electric field amplitudes for a fixed magnetic field strength is consistent with the key property of BernsteinGreene-Kruskal (BGK) solitary waves whose widths and potential amplitudes are constrained by inequalities (Chen and Parks, 2002a,b;Muschietti et al, 2002;Chen et al 2004). For a given size of a BGK solitary structure, there is a continuous range of allowed potential amplitudes, and vice versa.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…3(a)-4(b). The large spread in the electric field amplitudes for a fixed magnetic field strength is consistent with the key property of BernsteinGreene-Kruskal (BGK) solitary waves whose widths and potential amplitudes are constrained by inequalities (Chen and Parks, 2002a,b;Muschietti et al, 2002;Chen et al 2004). For a given size of a BGK solitary structure, there is a continuous range of allowed potential amplitudes, and vice versa.…”
Section: Discussionmentioning
confidence: 73%
“…However, no observational studies on how bipolar IES characteristics depend on the local magnetic field strength have been carried out, and there have been no systematic studies on tripolar IES. Most theories of IES provide only analytical solutions for either purely one dimension (Muschietti et al, 1999a,b) or strong magnetic field where the cyclotron radius has been taken as zero (Schamel, 1986;Muschietti et al, 2002;Chen and Parks, 2002a,b;Chen et al, 2004). On the other hand, in three-dimensional unmagnetized plasmas, it has been shown that fully localized solitary wave solutions do not exist if the ambient plasma is isotropic (Chen, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…They continuously merge with each other and at a later time, only few electron holes are left and they decay by emitting low-frequency electrostatic whistler waves just above the lower hybrid frequency (Singh, 2003). Recently, Muschietti et al (2002) have given a 3-D Bernstein-Greene-Kruskal (BGK) model to explain stretched solitary waves along the magnetic field lines observed in the downward current regions of the auroral zone. A full kinetic theory would be required to explain all features of the observed solitary structures.…”
Section: Discussionmentioning
confidence: 99%
“…Usually, electron holes evolve in the interaction of hot and cold electron plasmas; they are known as nonlinear BGK modes (Omura et al, 1996;Muschietti et al, 1999Muschietti et al, , 2002. The property of two electron temperatures populations allows for electron acoustic turbulence which has similar properties as ion acoustic waves.…”
Section: Introductionmentioning
confidence: 99%